Which factor is more important: Intensity or duration of episodic heat stress on broiler chickens?. (July 2021) - Iyasere, O.S.; Bateson, M.; Beard, A.P.; Guy, J.H.
Abstract: With the current global warming, there is a predicted increase in frequency, intensity and duration of heat waves in future. Little is known of how this could affect the welfare of broiler chickens. Sixty-four broiler chickens were subjected to either high heat stress (HHS; 32 °C, 70% RH for 3 h), moderate heat stress (MHS; 30 °C, 70% RH for 6 h), or normal conditions (NC: 20 °C, 50% RH for 6 h) for two consecutive days. On both days, the temperature–ID chips on all chipped birds were scanned during pre-heat stress (PrHS), end of 3 h (3HS) and 6 h (6HS) of heat stress using a pocket reader. Half of the chip birds' CBT was measured at the end of each hour of heat stress (HS: 1 st -3 rd hour). Surface body temperatures (SBTs) from under the wing (WT), feet (FT), cloaca (CLT) and comb (CT) were measured. Blood samples, feed intake, daily weight gain and mortality was also monitored. Data was analysed using General Linear Model and simple linear regression. At 3HS, CBT/ΔCBT and all SBTs showed this trend: HHS>MHS>NC (P<0.001). The regression equations to predict ΔCBT in HHS and MHS are ΔCBT = 0.917 + 0.663 h, P<0.05 and ΔCBT = 0.371 + 0.338 h, P<0.05 respectively. Blood pH, pCO2, iCa, HCO3 - and TCO2 showed same trend: HHS, MHS > NC (P<0.05). Comparing HHS for 3 h with MHS and NC for 6 h shows that CBT/ΔCBT, WT and CLT in HHS, MHS>control (P<0.001) while FT and CT showed a different trend (HHS > MHS > NC, P<0.001). pCO2, feed intake and daily weight gain showed same trend (HHS, MHS > control). Temperature-ID chip (a less invasive technique) gave CBT/ΔCBT values that corresponded with the degree of heat stress experienced by the birds. Broilers were more tolerant to MHS than HHS after 3 h but MHS for 6 h and HHS for 3 h had similar impact. Highlights: We established equations to predict change in core body temperature (ΔCBT) of chickens to high and moderate heat stress. The equations for high and moderate heat stress are ΔCBT=0.917+0.663h, P<0.05 and ΔCBT= 0.371+0.338h, P<0.05 respectively. After 3 h, CBT/ΔCBT and all surface body temperatures were greater (P<0.001) in high than moderate heat stress conditions. After 3h, all haematological parameters of the chickens were similar in high and moderate heat stress conditions. Moderate heat stress for 6 h or high heat stress for 3 h had similar impact on broiler welfare.